E-063 Cardiothoracic surgery does not pose significant risk of aneurysmal subarachnoid hemorrhage. (16th November 2010) - Moskowitz, S; Ching, E Cheng; Teng, Q; Hui, F
Abstract : Objective: Neurologic imaging prior to cardiac surgery often identifies incidental intracranial vascular pathology. The risk of hemorrhage from these lesions during an open cardiothoracic surgical procedure is unknown, preventing appropriate patient and surgeon counseling. We sought to identify the risk of aneurismal subarachnoid hemorrhage (SAH) in this population. Background: Patients undergoing cardiothoracic surgery often sustain significant hemodynamic fluctuations during and after their procedure. Since the incidence of cerebral aneurysms is estimated as 1–8% based on non-invasive imaging and autopsy studies, the number of patients harboring aneurysms is significant. It is unknown whether the cardiothoracic procedure impacts on the risk of aneurysm rupture. Methods: A prospective database of all cardiothoracic procedures is maintained for a large tertiary care center. Demographic, clinical, procedural and complication data are routinely collected. Data from this were reviewed for all procedures between 2001 and 2009 and neurologic complications identified. All identified strokes were reviewed for ischemia or hemorrhage, and the imaging reviewed for all hemorrhages to describe the pattern with focus on SAH and potential for aneurysms as contributory. Results: In this time period, over 10 000 procedures were performed. Neurologic events occurred in 617, of which 71 were hemorrhages. Hemorrhagic transformation of an ischemic stroke accounted for 49 (HI-1, 27; HI-2, 10; PH-1, 8; PH-2, 4). Two subdural hematomas were identified and nine intraparenchymal hemorrhages were seen. SAH occurred in 11, consisting of three as a direct result of a complication from intra-arterial thrombectomy. Seven were small convexity bleeds for which three had vascular imaging performed (all negative). One SAH was the result of a fusiform supraclinoid mycotic aneurysm which developed as a result of bacterial endocarditis. This aneurysm was not present on preoperative vascular imaging and required vessel sacrifice as it continued to grow rapidly and ruptured. No cases of SAH associated with a saccular aneurysm were identified. The incidence of cerebral aneurysms of 1–9% suggests that in this population, 100–900 aneurysms should exist. With no SAH cases identified, the periprocedural risk from aneurysm rupture is less than 0.01–0.001%. Conclusions: Aneurysm SAH as a direct result of open cardiothoracic surgery represents a very small risk. Consideration for management should be driven by cardiac indications with insignificant additional risk added by the incidental cerebral aneurysm found preoperatively.